The Effect of Husband Support During Labor on the Duration of the First Stage of Labor and Anxiety Levels Among Primigravida Mothers at Clinic X - Sri Wulan; Novensi Zalukhu; Selvi; Dewi Ramadani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Childbirth is a physiological process that often leads to anxiety, particularly among primigravida mothers who have no prior experience with labor. Elevated anxiety levels may influence uterine contractions and potentially prolong the duration of the first stage of labor. One non-pharmacological approach to reducing maternal anxiety is emotional support from the husband during the childbirth process. The presence of the husband can provide a sense of security, enhance comfort, and increase the mother’s confidence, thereby facilitating a smoother labor process. Objective: This study aimed to determine the effect of husband’s companionship during labor on the duration of the first stage of labor and the anxiety levels of primigravida mothers at Clinic X in 2026. Methods: This study employed a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 14 primigravida mothers selected through purposive sampling. Anxiety levels were measured using an anxiety questionnaire, while the duration of the first stage of labor was observed using a partograph. Data were analyzed using the Paired Sample t-test. Results: The mean maternal anxiety score before the husband’s companionship was 28.64 and decreased to 19.21 after the intervention. The average duration of the first stage of labor before the intervention was 9.14 hours and decreased to 7.36 hours after the intervention. Statistical analysis showed a p-value of 0.001 (p < 0.05), indicating a significant effect. Conclusion: Husband’s companionship during labor significantly reduces maternal anxiety and shortens the duration of the first stage of labor among primigravida mothers. Recommendation: Health care providers are encouraged to promote the active involvement of husbands as birth companions during the labor process to support maternal comfort and improve labor outcomes.